Perspectives on feminist political thought in European history : from the Middle Ages to the present - Akkerman, Tjitske; Stuurman, Siep (Routledge, 1998)
Spanning six centuries of political thought in European history, this book puts the ideas of thinkers from Christine de Pizan to Simone de Beauvoir in the broader contexts of their time. Conventional histories of political thought have sometimes relegated feminist thinking to the footnotes. This text considers how feminism is central to key notions of modern political discourse such as autonomy, liberty and equality, and feminist discussions of morality have been linked to major currents in political thought such as republicanism, civic humanism and romanticism. This collection of essays aims to show that feminism is not a variant of modern radical discourse but is a mode of analyzing the issues of authority, power and virtue that have been at the heart of European political thought from the Middle Ages.